1981
DOI: 10.1002/cne.901990304
|View full text |Cite
|
Sign up to set email alerts
|

Intracortical arborizations and receptive fields of identified ventrobasal thalamocortical afferents to the primary somatic sensory cortex in the cat

Abstract: The intracortical arborizations of neurons from the ventroposterolateral thalamic nucleus (VPL) in the cat were studied by intraaxonal injections of horseradish peroxidase (HRP) following identification of their receptive fields. In the primary somatic sensory cortex (SI) VPL cells terminated in different cytoarchitectonic areas according to their receptive field modality. Fibers excited by deep tissue or joint rotation arborized preferentially in area 3a. Those responding tonically to cutaneous stimuli were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…These rods are anatomically defined by the terminal arbors of axons from the medial lemniscus (Hirai et al 1988; Rausell and Jones 1991) and are physiologically defined by neuronal responses to innocuous stimulation (Jones et al 1982; Kaas et al 1984; Lenz et al 1988b; Morrow and Casey 1992;Tremblay et al 1993). Thalamo-cortical fibers parallel the rod from which they originate (Landry and Deschenes 1981) and terminate in cortical columns (Jones et al 1982), consistent with the modality-specific organization in the primary sensory cortex (Jones et al 1982;Kaas 1983;Rausell et al 1992). Similarly, thalamic rods subserve different cutaneous structures (e.g., glabrous or hairy skin) consistent with the place-specific organization in the primary sensory cortex (Jones et al 1982 (Davis et al 1999;Ohara and Lenz 2003).…”
Section: Introductionsupporting
confidence: 61%
“…These rods are anatomically defined by the terminal arbors of axons from the medial lemniscus (Hirai et al 1988; Rausell and Jones 1991) and are physiologically defined by neuronal responses to innocuous stimulation (Jones et al 1982; Kaas et al 1984; Lenz et al 1988b; Morrow and Casey 1992;Tremblay et al 1993). Thalamo-cortical fibers parallel the rod from which they originate (Landry and Deschenes 1981) and terminate in cortical columns (Jones et al 1982), consistent with the modality-specific organization in the primary sensory cortex (Jones et al 1982;Kaas 1983;Rausell et al 1992). Similarly, thalamic rods subserve different cutaneous structures (e.g., glabrous or hairy skin) consistent with the place-specific organization in the primary sensory cortex (Jones et al 1982 (Davis et al 1999;Ohara and Lenz 2003).…”
Section: Introductionsupporting
confidence: 61%
“…Three independent lines of evidence suggest that the profiles described here are a valid measure of thalamocortical input. First, axon-filling studies in visual cortex (Humphrey et al, 1985) and somatic sensory cortex (Landry and Deschênes, 1981) of physiologically identified afferents describe many features like those in the present study. They did not discern the class of giant axons as- Mesulam and Pandya (1973;monkey) Fink-Heimer, Nauta…”
Section: Methodological Considerationsmentioning
confidence: 71%
“…22 Projections between thalamus and cortex were also topographic, but more divergent, consistent with anatomical studies. 29,33,40 The anatomical bases underlying this type of connectivity were detailed in previous papers. 19,22 In a previous study, 19 it was shown that calculating average membrane potentials using an intersite distance of 11 cells led to similar propagation velocity as in experiments, suggesting that this distance roughly corresponds to the interelectrode distance of 1 mm in the experimental setup.…”
Section: Computational Modelsmentioning
confidence: 99%